Simulation of Wood Combustion in PATO Using a Detailed Pyrolysis Model Coupled to fireFoam - Hermes Scandelli (MDPI AG, 2021)
The numerical simulation of fire propagation requires capturing the coupling between wood pyrolysis, which leads to the production of various gaseous species, and the combustion of these species in the flame, which produces the energy that sustains the pyrolysis process. Experimental and numerical works of the fire community are targeted towards improving the description of the pyrolysis process to better predict the rate of production and the chemical nature of the pyrolysis gases. We know that wood pyrolysis leads to the production of a large variety of chemical species: water, methane, propane, carbon monoxide and dioxide, phenol, cresol, hydrogen, etc. With the idea of being able to capitalize on such developments to study more accurately the physics of fire propagation, we have developed a numerical framework that couples a detailed three-dimensional pyrolysis model and fireFoam. In this article, we illustrate the capability of the simulation tool by treating the combustion of a wood log. Wood is considered to be composed of three phases (cellulose, hemicellulose and lignin), each undergoing parallel degradation processes leading to the production of methane and hydrogen. We chose to simplify the gas mixture for this first proof of concept of the coupling of a multi-species pyrolysis process and a flame. In the flame, we consider two separate finite-rate combustion reactions for methane and hydrogen. The flame evolves during the simulation according to the concentration of the two gaseous species produced from the material. It appears that introducing different pyrolysis species impacts the temperature and behavior of the flame.